Peran Minat Beli Sebagai Variabel Intervening Pada Pengaruh Persepsi Harga, Kualitas Produk, dan Promosi Terhadap Keputusan Pembelian - Zararosa, Gracia Angel; Khasanah, Imroatul (Faculty of Economics and Business | Universitas Diponegoro, 2023)
The food and beverage industry is growing rapidly. The attractiveness of this industry in Indonesia is very strong, this makes business opportunities in the food and beverage sector have mushroomed and are promising. Supported by the increasing number of franchise business offers that are quite easy to do and new types of culinary such as contemporary drinks, coffee shops, and so on. Old culinary types such as processed chicken, pizza, and other fast food also innovate unique flavors and appearances to attract the millennial generation's interest. One of them is Pizza Hut. According to financial report data, sales have decreased since 2020 and 2021, in addition, data on the Top Brand Index has decreased for 3 consecutive years in 2017, 2018, and 2019. In addition, there are inconsistencies in the results of research on the relationship of Product Quality to Purchasing Decisions. Because of these problems, this research was carried out. This study aims to analyze and prove the influence of Price Perception, Product Quality, and Promotion on Purchasing Decisions through Buying Interest as an Intervening Variable (Study on Pizza Hut Customers in Semarang City.)